Plasmid content of a clinically relevant Klebsiella pneumoniae clone from the Czech Republic producing CTX-M-15 and QnrB1 - Dolejska, Monika; Villa, Laura; Dobiasova, Hana; Fortini, Daniela; Feudi, Claudia; Carattoli, Alessandra (Antimicrobial agents and chemotherapy, 2013)
The entire plasmid content of a multidrug-resistant, CTX-M-15-producing Klebsiella pneumoniae ST416 clone was investigated. Two FII(K) plasmids, pKDO1 (127 kb) and pKPN-CZ (207 kb), were identified and found to carry a formidable set of genes conferring resistance to toxic compounds, metals, and antimicrobial drugs and exhibiting novel features putatively associated with adaptation and fitness of the bacterium in the human host.
Keywords: Microbial Sensitivity Tests; Metals; mnohočetná bakteriální léková rezistence; Molecular Sequence Data; molekulární sekvence - údaje; Klebsiella pneumoniae; mikrobiální testy citlivosti; Anti-Infective Agents; antiinfekční látky; Klebsiella Infections; kovy; plazmidy; bakteriální proteiny; infekce bakteriemi rodu Klebsiella; Drug Resistance, Multiple, Bacterial; beta-laktamasy; Czech Republic; Bacterial Proteins; beta-Lactamases; Česká republika; Plasmids